Metabolic syndrome is associated to high-sensitivity cardiac troponin T elevation. (17th February 2019) - Milwidsky, Assi; Fisher, Eyal; Brzezinski, Rafael Y.; Ehrenwald, Michal; Shefer, Gabi; Stern, Naftali; Shapira, Itzhak; Zeltser, David; Rosenbaum, Zach; Greidinger, Dahlia; Berliner, Shlomo; Shenhar-Tsarfaty, Shani; et al.
Abstract: Introduction: Metabolic syndrome (MetS) and high-sensitivity cardiac troponin T (hs-TnT) are associated with higher risk for cardiovascular diseases (CVD). Our aim was to assess the relation between hs-TnT elevation and MetS in a general population sample. Materials and methods: Individuals participating in an annual health survey program between 2010 and 2016 were included in the study. Blood samples including hs-TnT levels were collected. The study population was divided into three groups based on hs-TnT levels – undetectable (<5  ng/L), intermediate (5–14  ng/L) and elevated (>14  ng/L). Results: A total of 5994 subjects were included in the study, the mean age was 48.5 and 4336 (72%) were males. Compared with subjects with undetectable hs-TnT the prevalence of MetS was higher in those with detectable and elevated levels – 392 (10%) vs. 270 (15%) and 51 (33%), respectively ( p   <  0.001). In a multivariate model adjusted for age, gender and multiple co-morbidities, the number of MetS components and presence of MetS were significantly associated with an increased risk for detectable hs-TnT levels (OR  =  1.02 {for each component}; 95% CI [1.00–1.05], p   =   0.04) and (OR  =  1.13; 95% CI [1.07–1.2], p   <  0.001) respectively. Only the waist, glucose and hypertension components of the MetS were significantly associated with elevated troponin. Conclusions: The MetS and its distinct components have a cumulative impact on hs-TnT levels in apparently healthy subjects.